Pursuing equity in cancer care: implementation, challenges and preliminary findings of a public cancer referral center in rural Rwanda. Issue 1 (December 2016) - Tapela, Neo; Mpunga, Tharcisse; Hedt-Gauthier, Bethany; Moore, Molly; Mpanumusingo, Egide; Xu, Mary; Nzayisenga, Ignace; Hategekimana, Vedaste; Umuhizi, Denis; Pace, Lydia; Bigirimana, Jean; Wang, JingJing; et al.
Abstract Background Cancer services are inaccessible in many low-income countries, and few published examples describe oncology programs within the public sector. In 2011, the Rwanda Ministry of Health (RMOH) established Butaro Cancer Center of Excellence (BCCOE) to expand cancer services nationally. In hopes of informing cancer care delivery in similar settings, we describe program-level experience implementing BCCOE, patient characteristics, and challenges encountered. Methods Butaro Cancer Center of Excellence was founded on diverse partnerships that emphasize capacity building. Services available include pathology-based diagnosis, basic imaging, chemotherapy, surgery, referral for radiotherapy, palliative care and socioeconomic access supports. Retrospective review of electronic medical records (EMR) of patients enrolled between July 1, 2012 and June 30, 2014 was conducted, supplemented by manual review of paper charts and programmatic records. Results In the program's first 2 years, 2326 patients presented for cancer-related care. Of these, 70.5 % were female, 4.3 % children, and 74.3 % on public health insurance. In the first year, 66.3 % (n  = 1144) were diagnosed with cancer. Leading adult diagnoses were breast, cervical, and skin cancer. Among children, nephroblastoma, acute lymphoblastic leukemia, and Hodgkin lymphoma were predominant. As of June 30, 2013, 95 cancer patients had died. Challenges encountered include documentation gaps and staff shortages. Conclusion Butaro Cancer Center of Excellence demonstrates that complex cancer care can be delivered in the most resource-constrained settings, accessible to vulnerable patients. Key attributes that have made BCCOE possible are: meaningful North–south partnerships, innovative task- and infrastructure-shifting, RMOH leadership, and an equity-driven agenda. Going forward, we will apply our experiences and lessons learned to further strengthen BCCOE, and employ the developed EMR system as a valuable platform to assess long-term clinical outcomes and improve care.